Change in the repair cycle of excavator fingers - Levashova E.E. (Горное оборудование и электромеханика)
The volumes of mined coal are affected by both the amount mining equipment (distribution by excavator-truck complex) and reliability associated with the smooth operation the open pit. Due to the circumstances of the country that had to be faced, the tendency to update the excavator fleet is weak, so maintaining the technical condition equipment becomes a priority. The article presents the results of studies the developed technology for restoring the fingers quarry excavators buckets, which consists in surfacing a special layer and subsequent local heat treatment, such studies as spectral-acoustic analysis, microhardness measurement, metallographic studies were carried out, according to the results it is clear that the use of the new technology leads to an increase in the hardness and wear resistance of the surface layer. Due to the change in the manufacturing technology, according to the calculated data, the resource part increases, which will lead to a change in the structure the repair cycle, which entails the transition parts from current repair T1 to T2. Changes in the repair cycle are graphically depicted, calculations of time and financial costs for repair of three options for performing routine repair of pins (axles) of quarry excavators during the implementation of technology or performing repairs without changing the technology are performed. The calculation established that financial costs can be reduced by 60–97%.